Early-Life Stressors, Personality Development, and Fast Life Strategies: An Evolutionary Perspective on Malevolent Personality Features - Csathó, Árpád; Birkás, Béla (Frontiers in Psychology, 2018)
Life history theory posits that behavioral adaptation to various environmental (ecological and/or social) conditions encountered during childhood is regulated by a wide variety of different traits resulting in various behavioral strategies. Unpredictable and harsh conditions tend to produce fast life history strategies, characterized by early maturation, a higher number of sexual partners to whom one is less attached, and less parenting of offspring. Unpredictability and harshness not only affects dispositional social and emotional functioning, but may also promote the development of personality traits linked to higher rates of instability in social relationships or more self-interested behavior. Similarly, detrimental childhood experiences, such as poor parental care or high parent-child conflict, affect personality development and may create a more distrustful, malicious interpersonal style. The aim of this brief review is to survey and summarize findings on the impact of negative early-life experiences on the development of personality and fast life history strategies. By demonstrating that there are parallels in adaptations to adversity in these two domains, we hope to lend weight to current and future attempts to provide a comprehensive insight of personality traits and functions at the ultimate and proximate levels.